Integrasi Fiqh al-Bi'ah dan Praktik Lingkungan Adat: Studi terhadap Tradisi Pa'jukukang di Kabupaten Bantaeng - Tahir, Muhammad; Maloko, M Thahir; Talli, Abdul Halim (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to conduct a critical study of the pa'jukukang tradition in the traditional rituals of the Bugis-Makassar community from the perspective of environmental fiqh, focusing on the identification of the ecological impact caused and the relevance of Islamic sharia values in regulating human relations with nature. This research is a field study with a qualitative approach, using descriptive-analytical methods and sharia approaches to examine in depth the Islamic values contained in these cultural practices. Data was obtained through participatory observation, in-depth interviews, and documentation, then analyzed thematically. The results of the study show that the pa'jukukang tradition consists of four main stages: appasulu pangngajai, akkawaru, kalau'u ri pa'jukukang, angnganre ta'bala'na, and angnganre raja'na. The implementation of this tradition has an ambivalent impact on the environment: on the one hand, there are the values of preservation and respect for nature; But on the other hand, some technical practices have the potential to cause pollution or overexploitation of natural resources. From the perspective of environmental jurisprudence, the implementation of this tradition can be reviewed through the basic principles of Islamic ecological ethics, namely spirituality as the basis of ecological behavior; iḥtirām wa ḥiẓ al-bi'ah (respect and protection of the environment); istikhlāf wa al-amānah (Caliph and Trust); al-mīzān (balance); al-'adl wa al-iḥsān (justice and goodness); al-maṣlaḥah al-'āmmah (public good); lā tufsidū fī al-arḍ (prohibition of doing damage to the earth); and the principle of sustainability. Therefore, it is necessary to mainstream environmental jurisprudence in the implementation and preservation of the pa'jukukang tradition as a form of harmonization between local cultural values and Islamic teachings in maintaining environmental sustainability.